The SMART Practice of Scholarly Practice. (August 2013) - Lombardozzi, Catherine
The Problem: Scholar-practitioners can be more successful than their less grounded peers; yet engaging in scholarly practice is not a guarantee of success in a business environment. The cases in this issue provide examples of scholarly practice, but don't necessarily provide actionable advice on how it is effectively accomplished. The Solution: This article derives a framework for SMART (Scholarly, Macro, Aligned, Realistic, and Tested) practice that draws from the literature on scholarly practice and the literature on practicing HRD with a business mind-set to generate practices that are effective in organizations. The cases in this issue provide examples of these behaviors. The Stakeholders: The SMART framework supports practitioners who want to increase their effectiveness at integrating theory and research into practice and HRD faculty who want to provide guidance on successful scholarly practice. In the end, leaders that might desire a more theory- or evidenced-based approach to HRD will benefit from having more savvy HRD practitioners.